Analisis Kesulitan Membaca pada Siswa Kelas III Sekolah Dasar: Studi Kasus pada Siswa Kelas III di SD Negeri Kembaran - Lintang Dwi Ajrianingrum; Badarudin Badarudin (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
This research was made with the aim of knowing the reading difficulties faced by students from the impact of the COVID-19 pandemic in 2019. This research uses a type of qualitative research with a case study method. Data collection techniques used observation, interviews and documentation. The research subjects were 6 students in class III of SD Negeri Kembaran in 2023. The results of this study are reading difficulties experienced by students such as not recognising some consonant and vowel letters, difficulty distinguishing letters that have the same shape, reading is still spelled out, stammering, slow reading, difficulty in stringing words, omission and change of letters, reading does not pay attention to punctuation and does not understand the content of the reading text. Factors causing reading difficulties such as intellectual factors or students' ability to read, environmental factors such as students' background and experience and socio-economic factors. As well as psychological factors in the form of student motivation, interest, emotions and student confidence. Teachers' efforts to overcome reading difficulties experienced by students by using the repetition method with visual media such as reading books and reading cards.